(untitled) (Journal of the College of Basic Education, 2023)
In this study, we are studying the effect of annealing temperature on the structure and the optical properties of CdS:Cu thin films which were prepared by thermal evaporation technique in vacuum with rate deposition (4.1A°/sec) and thickness(=400nm),all these samples have been annealed at different annealing temperatures (RT,373,423 and 473 K). The structural properties of the films have been studied by using X-ray diffraction. The optical measurements indicate that CdS:Cu films have direct optical energy gap (E,""), and it decreases from 2.43 eV to 2.37 eV with the increase of annealing temperatures (R.T — 473)K. The optical constants refractive index (n), extinction coefficient (k),absorption coefficient (a) and dielectric constants (€, and €;) were also studied.